Implementation of project monitoring and controlling in construction in Pahang - Ahmad Al Asfahan, Abdull Rahim (2015)
This research examine the implementation of project monitoring and controlling in construction industry in Kuantan Pahang. Monitor and control are very important to the construction industry, in order to keep the construction as planning. However, there are still challenges that construction companies need to face. The literature give some review on monitoring and controlling that has been conducted by other researchers. This research is conducted to measure the level of monitoring and controlling in Construction Company in Kuanatn, Pahang Darul Makmur. The research is conducted by distributing the questionnaire to the contractor G7 of Construction Company around Kuantan, Pahang. This research finds that the company in Kuantan, Pahang are adopted monitor and control tools and faced some challenges while conduct the monitoring and controlling.